Evodiamine protects against airway remodelling and inflammation in asthmatic rats by modulating the HMGB1/NF-κB/TLR-4 signalling pathway. (1st January 2021) - Wang, Qiong; Cui, Yubao; Wu, Xufeng; Wang, Junfang
Abstract: Context: Evodiamine, which is isolated from Evodia rutaecarpa (Rutaceae), possess strong anti-inflammatory, immunomodulatory, and antibacterial properties. Objective: The protective effects of evodiamine in asthma were evaluated. Materials and methods: Thirty-two Sprague-Dawley (SD) rats were used, asthma was induced by injecting intraperitoneally with a mixture of Al(OH)3 (100 mg) and ovalbumin (OA; 1 mg/kg), further exposing them to a 2% OA aerosol for 1 week. All animals were divided into four groups: control, asthma, and evodiamine 40 and 80 mg/kg p.o. treated group. Serum levels of inflammatory cytokines, interferon gamma (IFN-γ), and immunoglobulin E (IgE) and infiltrations of inflammatory cells in the bronchoalveolar lavage fluid (BALF) of the animals were determined. The thickness of the smooth muscle layer and airway wall in the intact small bronchioles of asthmatic rats was examined as well. Results: Cytokine levels in the serum and BALF were lower in the evodiamine-treated group than in the asthma group. Evodiamine treatment reduced IgE and IFN-γ levels as well as the inflammatory cell infiltrate in the lung tissue of asthmatic rats. The thickness of the smooth muscle layer and airway wall of intact small bronchioles was less in the evodiamine-treated group than in the asthma group. Lower levels of TLR-4, MyD88, NF-κB, and HMGB1 mRNA in lung tissue were measured in the evodiamine-treated group than in the asthma group. Discussion and conclusion: The effect of evodiamine treatment protects the asthma, as evodiamine reduces airway inflammation and remodelling in the lung tissue by downregulating the HMGB1/NF-κB/TLR-4 pathway in asthma.